Perceptions and Definitions of Power Within the Context of HIV-Negative Male Couples’ Relationships - Mitchell, Jason W. (Am J Mens Health, 2016)
Examining dynamics within relationships is critical for development of effective HIV prevention interventions for male couples. The dynamic of power has received little attention in research with male couples, though power has been reported to affect HIV risk among heterosexual couples. To help address this knowledge gap, the present cross-sectional analysis used mixed methods with dyadic data from 142 HIV-negative male couples to (1) assess partnered men’s perception of who has the most power in their relationship and why, (2) examine whether partners concur about who has the most power and their reasoning for this selection, and (3) assess whether male couples’ concurrence about who has the most power is associated with their engagement of condomless anal sex within and/or outside the relationship, type of relationship, and aspects of their sexual agreement. Individual- and couple-level responses about who has the most power were quantitatively assessed, whereas for why, their responses were coded qualitatively. Fifty-six percent of couples concurred about who has the most power in their relationship and of these, many said it was equal. Regarding why, themes of responses ranged from “compromise” and “shared responsibility” for those who concurred about who has the most power versus “dominant/compliant personality” and “money” among the couples who disagreed about who has the most power in their relationship. Concordance about who has the most power was only associated with condomless anal sex within the relationship. Further research is warranted to examine how power may affect other dynamics of male couples’ relationships and risk-related behaviors.